Analisis Hasil Penilaian Kinerja Guru - Yuningsih, Ida; Sunhaji, Sunhaji (Pusat Studi Pendidikan Kreatifitas Anak Wadas Kelir Purwokerto, 2021)
This research shows that the implementation of Teacher Performance Appraisal in schools has been implemented but has never been followed up by analyzing the results. Analysis is very important for schools to compile a Sustainable Professional Development program for teachers and as a tool for evaluating the implementation of Teacher Performance Appraisals in order to achieve better education quality. From the results of observations and interviews, there were assessors who were not objective, the value of Teacher Performance Appraisal with certified physical evidence was not yet appropriate. The average result of the Subject Teacher Performance Appraisal is 87% (good) and the Counseling Guidance is 88% (good). Average Teacher Performance Appraisal in pedagogic competence subjects 83% (good) and Counseling Guidance 97% (very good), subject teacher personality competence 98% (very good) and Counseling Guidance 100% (very good), social competence of subject teachers lesson 86% (good) and Counseling Guidance 83% (good), as well as the professional competence of subject teachers 83% (good) and Counseling Guidance 79% (good). However, there are several competency indicators for subject teachers whose mastery is 75% (sufficient) and Counseling Guidance 50% (moderate). Even though the results of the Teacher Performance Assessment have been good, the principal needs to control the implementation and reporting so that the results are more credible, can be accounted for, not only for aborting obligations as well as one of the requirements for submitting credit scores for teachers.